Anthropometric evaluation of male wrestlers - Paduraru, D. (2001)
Biological development and body composition was evaluated by measuring physical parameters of the best male wrestlers (Greek-Roman) from the Romanian Olympic team. This anthropometric study was made to estimate a number of anthropometric markers of training of 25 male wrestlers of top level, who were studied following ISAK protocols, using a formulae and the result were statistically analysed. The participant`s physical characteristics: height (Ht), weight (Wt), perimeters, skinfolds (SF) abdominal (ASF), suprailiac (SISF), subscapular (SSK), triceps (TSF), thigh (TISF) were measured by an accredited anthropometrist. Bodyfat mass was calculated using the formulae put forward by BROZECK&KEYS (1951). After measuring, 25 wrestlers with the age (Ag) range 18.8-31.5 years, mean 23.9y., sport history (SH) range 5-23 years, mean 12.17y., height (Ht) 158.4-194.7 cm, mean 172.9 cm, weight (Wt) range 58-116.5 kg, mean 82.6 kg, body mass index (BMI) range 23.11-32.61, mean 24.98, bone development index (BDI) range 41.16-47.94, mean 44.82, body fat mass (BFM kg) range 6.7-24.23 kg, mean 10.74, body fat mass (BFM %) range 3.75-20.08% mean 11.75%, fat-free mass (FFM kg) range 52.05-92.38 kg, mean 68.34 kg, fat free mass (FFM %) range 79.20-89.27%, mean 86.89. With regard to skinfolds thickness the triceps skinfold recorded the lowest values followed by subscapular and tight skinfolds. Variance suggests that anthropometric parameters other than weight (Wt) and height (Ht) may be useful to estimate the level of training in professional wrestlers (Greek-Roman).